Acute gastric dilatation after excessive consumption of traditional Chinese medicine: a case report - Zeng, Tao; Chen, Zi-liang; Zhou, Yao-hui; liu, Wei-qi; Chen, Jian; Lu, Jian-hui; Lin, Jia-hao (Frontiers in Medicine, 2025)
IntroductionAcute gastric dilatation (AGD) is a rare but clinically significant condition characterized by abnormal enlargement of the stomach. It can lead to serious complications such as gastric necrosis, perforation, and respiratory failure if not promptly managed. AGD has been associated with mechanical obstructions, binge eating, and systemic conditions like diabetes mellitus. However, AGD induced by excessive consumption of traditional Chinese medicine (TCM) has not been previously reported.Patient concernsA 40-year-old male with a history of chronic dyspepsia presented to the emergency department with recurrent vomiting. Over the 3 days prior to admission, he self-reported consuming approximately 3.5 liters of TCM liquid (about 1.1–1.3 liters per day). This attempt to alleviate his chronic dyspepsia symptoms failed to show the expected therapeutic effect. The patient denied experiencing headache, dizziness, chest pain, palpitations, abdominal pain, or diarrhea.DiagnosisAbdominal CT revealed significant gastric distension, and subsequent endoscopy showed pyloric ulcer with stenosis, gastric retention, chronic atrophic gastritis, and a relaxed cardia. Laboratory investigations indicated metabolic alkalosis, electrolyte imbalances, and signs of tissue hypoxia.InterventionsThe patient was immediately managed with nasogastric tube decompression, anti-infection therapy, gastric mucosal protection, fluid resuscitation, parenteral nutritional support, fasting, and gastrointestinal decompression.OutcomesThe patient’s symptoms and signs notably improved after these interventions. A follow-up CT scan demonstrated improved gastric dilation. At a 4-week follow-up, the patient reported complete resolution of vomiting and resumed normal oral intake. Repeat endoscopy showed healed pyloric ulcers and improved gastric motility. No adverse events (e.g., rehospitalization or medication intolerance) were reported during a 3-month follow-up period.ConclusionThis case highlights the necessity of including AGD in the differential diagnosis for patients presenting with frequent vomiting after excessive consumption of TCM. It underscores the importance of thorough evaluation to prevent misdiagnosis and severe complications. The case also emphasizes the need for caution when using TCM, especially in patients with organic lesions or pyloric obstruction.